Wiedza kobiet leczących się z powodu osteoporozy na temat ogólnej wiedzy o chorobie i czynników jej ryzyka = Knowledge of women treated for osteoporosis on the general knowledge about the disease and its risk factors - Katarzyna Pawlikowska-Łagód; Mariola Janiszewska; Ewelina Firlej; Olga Dąbska; Jarosław Sak (Kazimierz Wielki University, 2016)
Pawlikowska-Łagód Katarzyna, Janiszewska Mariola, Firlej Ewelina, Dąbska Olga, Sak Jarosław. Wiedza kobiet leczących się z powodu osteoporozy na temat ogólnej wiedzy o chorobie i czynników jej ryzyka = Knowledge of women treated for osteoporosis on the general knowledge about the disease and its risk factors. Journal of Education, Health and Sport. 2016;6(5):255-265. eISSN 2391-8306. DOI http://dx.doi.org/10.6084/m9.figshare.3382852 http://ojs.ukw.edu.pl/index.php/johs/article/view/3523     The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 25.04.2016. Revised 25.04.2016. Accepted: 17.05.2016.   Wiedza kobiet leczących się z powodu osteoporozy na temat ogólnej wiedzy o chorobie i czynników jej ryzyka   Knowledge of women treated for osteoporosis on the general knowledge about the disease and its risk factors   Pawlikowska-Łagód Katarzyna1, Janiszewska Mariola2, Firlej Ewelina2, Dąbska Olga3, Sak Jarosław1 Pawlikowska-Łagód Katarzyna1, Janiszewska Mariola2, Firlej Ewelina2, Dąbska Olga3, Sak Jarosław1   1Zakład Etyki i Filozofii Człowieka, Uniwersytet Medyczny w Lublinie 2Katedra Zdrowia Publicznego, Uniwersytet Medyczny w Lublinie 3Zakład Patologii i Rehabilitacji Mowy, Uniwersytet Medyczny w Lublinie   1Department of Ethics and Human Philosophy, Medical University of Lublin, Poland 2Faculty of Health Science, Medical University of Lublin, Poland 3Department of Pathology and Speech Rehabilitation, Medical University of Lublin           mgr Pawlikowska-Łagód Katarzyna1, dr n. o zdr. Janiszewska Mariola2, mgr Firlej Ewelina2, Dąbska Olga3, dr hab. n med. Sak Jarosław1 1Zakład Etyki i Filozofii Człowieka, Uniwersytet Medyczny w Lublinie 2Katedra Zdrowia Publicznego, Uniwersytet Medyczny w Lublinie 3Zakład Patologii i Rehabilitacji Mowy, Uniwersytet Medyczny w Lublinie   mgr Pawlikowska-Łagód Katarzyna1, dr n. o zdr. Janiszewska Mariola2, mgr Firlej Ewelina2, Dąbska Olga3, dr hab. n med. Sak Jarosław1 1Department of Ethics and Human Philosophy, Medical University of Lublin, Poland 2Faculty of Health Science, Medical University of Lublin, Poland 3Department of Pathology and Speech Rehabilitation, Medical University of Lublin           Słowa kluczowe: wiedza, osteoporoza, kobiety, czynniki ryzyka Keywords: knowledge, osteoporosis, women, risk factors   Streszczenie Osteoporoza stanowi jeden z istotnych problemów zdrowotnych, społecznych i ekonomicznych współczesnego świata. Jest chorobą obarczoną ryzykiem trwałego kalectwa i z powodu powikłań wcześniejszej śmiertelności.  Ryzyko zachorowania, dotyczące kobiet wzrasta głównie po 65 roku życia. Szacuje się, że na całym świecie osteoporoza dotyka 200 mln kobiet, z których około 20 - 25% dozna urazu w postaci złamania kości. Biorąc pod uwagę fakt wydłużenia życia statystycznej Polki, należy zauważyć, że spowoduje to wzrost liczby kobiet chorujących na osteoporozę oraz złamań będących jej następstwem. Zwiększą się koszta medyczne i  społeczne związane z leczeniem choroby i jej następstw. Bezsprzecznie możemy stwierdzić, że wiedza na temat osteoporozy a zwłaszcza czynników jej ryzyka i profilaktyki powinien być dobrze znany środowiskom związanym z opieką zdrowotną, a przede wszystkim osobom narażonym na jej rozwój i konsekwencje. W związku z powyższym zajmowanie się tematyką osteoporozy wydaje się być jak najbardziej zasadne, na co wskazują liczne dane dotyczące zachorowalności, świadczące o fakcie zwiększania się liczby osób chorych na osteoporozę w krajach Unii Europejskiej i w Polsce. Cel pracy: Celem pracy było zbadanie ogólnego poziomu wiedzy o chorobie i czynnikach jej ryzyka wśród kobiet leczących się z powodu osteoporozy Materiał i metody: Grupę badaną stanowiło 137 pacjentek poradni leczenia osteoporozy w Lublinie. Wiek badanych mieści się w przedziale od 38 do 91 lat (M= 61,6; SD=10,6 ). Badania prowadzone były w Wojewódzkim Szpitalu Specjalistycznym w Lublinie oraz Niepublicznym Zakładzie Opieki Zdrowotnej REUMED w Lublinie w okresie od lutego do kwietnia 2015 roku. Do pomiaru zmiennych wykorzystano kwestionariusz ankiety własnego autorstwa zawierający pytania pozwalające ocenić ogólną wiedzę badanych na temat istoty choroby oraz wiedzę na temat czynników ryzyka.    Wyniki: Badane wykazują się średnim poziomem wiedzy o osteoporozie. Miejsce zamieszkania różnicuje istotnie poziom wiedzy respondentek o osteoporozie. Osoby mieszkające na wsi charakteryzują się słabszą wiedzą, niż mieszkanki miast. Badane wykazywały się przeciętną wiedzą o czynnikach ryzyka wpływających na rozwój osteoporozy. Najczęściej podawanymi przez badane czynnikami ryzyka było małe pokrycie wapnia w pożywieniu, płeć żeńska oraz wczesna menopauza.   Summary Osteoporosis is one of the important health, social and economic world today. It is burdened with the risk of disease and permanent disability due to complications early mortality. The risk relating to women increases mainly after 65 years. It is estimated that worldwide osteoporosis affects 200 million women, of which about 20 - 25% will suffer a fracture of the bone. Given increasing life statistical Pole, it should be noted that this will increase the number of women suffering from osteoporosis and fractures that are its consequence. Will increase the cost of medical and social treatment-related disease and its consequences. Undoubtedly, we can say that knowledge of osteoporosis and in particular its risk factors and prevention should be familiar environments related to health care, and above all persons exposed to its development and consequences. Therefore, dealing with issues of osteoporosis seems to be the most reasonable, as evidenced by the numerous incidence data testifying to the fact of increasing the number of people suffering from osteoporosis in the European Union and in Poland. The aim of the study was to assess the general level of knowledge about the disease and its risk factors among women treated for osteoporosis. Materials and methods: The study group consisted of 137 patients, outpatient treatment of osteoporosis in Lublin. The age of patients is in the range from 38 to 91 years (M = 61.6; SD = 10.6). The research was conducted at the Provincial Specialist Hospital in Lublin and the Non-public Health Care REUMED in Lublin in the period from February to April 2015. For the measurement of the variables used by his own questionnaire containing questions to assess general knowledge of the respondents about the nature of the disease and knowledge of risk factors. Results: Both show the average level of knowledge about osteoporosis. Place of residence differentiate significantly the level of knowledge respondents about osteoporosis. People living in rural areas are characterized by a weaker knowledge than urban residents. The studied showed a significant knowledge of the risk factors affecting the development of osteoporosis.